1994
DOI: 10.1002/lsm.1900140409
|View full text |Cite
|
Sign up to set email alerts
|

Development and experimental in vivo validation of mathematical modeling of laser coagulation

Abstract: Most clinical procedures using the laser are based on thermal laser-tissue interactions. The treatment often consists of inducing damage of given degree and extent by heating the tissue. The aim of this study was to develop a model called HELIOS. The ability of HELIOS to predict thermal coagulation was evaluated by comparison with in vivo experimental results. Conversion of laser light in tissue was studied using the beam-broadening model. Temperature was described by the heat conduction equation solved using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Numerical modeling of the optical and thermal lasertissue interactions has proven to be a useful tool for the planning and optimization of many clinical procedures involving laser energy [10,[18][19][20]. However, simulation of the relatively new LCR procedures goes well beyond the scope of traditional opto-thermal models and requires consideration of thermally induced changes in the tissue mechanical state.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical modeling of the optical and thermal lasertissue interactions has proven to be a useful tool for the planning and optimization of many clinical procedures involving laser energy [10,[18][19][20]. However, simulation of the relatively new LCR procedures goes well beyond the scope of traditional opto-thermal models and requires consideration of thermally induced changes in the tissue mechanical state.…”
Section: Discussionmentioning
confidence: 99%
“…Beacco et al confirmed these observations by mathematical modelling. [11][12][13][14] Advantages of the combined energy of these two wavelengths are currently being seen in our patients at a clinical level because of the higher temperatures accumulating in the dermis, but without damaging the overlying epidermis. When the Nd:YAG laser is applied to IPLirradiated tissue, the process of tissue denaturation has already taken place, which occurs at temperatures in the range 50-65 ‡C and involves thermal breaking of the heatlabile hydrogen bonds between collagen fibrils caused by the IPL pulse in the dermal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Its objective is to raise the temperature of pathological tissues above cytotoxic temperatures (41-45°C) without overexposing healthy tissues [1][2][3][4]. Although difficult to achieve and maintain in a clinical setting, uniform temperature distributions, are significant during hyperthermia treatment [5] since the use of temperatures above 55°C may directly destroy tissues through thermal coagulation, as was illustrated by Beacco et al [6]. Temperature variations, which may be associated with the mechanisms of heat removal by the body and may sometimes be caused by inadequate heating technologies, are often heterogeneous, and can lead to defectively heated tissues, hot spots and potential burning.…”
Section: Introductionmentioning
confidence: 99%